?-acetato / ?-aqua bridged binuclear vic-dioxime complexes thermal, magnetic and spectral studies - Duman, Sibel; Şekerci, Memet (Chemical Society of Pakistan, 2015)
A new amino vic-dioxime ligand, N,N?-[3,3?-{ethane-1,2-di-yl-bis(oxy)bis(3,1-phenylene)}bis(N?-hydroxy-)2-(hydroxyimino)-acetimidamide] (LH4) was synthesized by reaction of 1,2-bis(m-aminophenoxy)ethane and anti-chloroglyoxime. Then, its Cu(II), Ni(II), Co(III) and Cd(II) complexes were synthesized by the ligand and Cu(AcO)2.H2O, Ni(AcO)2.4H2O, Co(AcO)2.4H2O and Cd(AcO)2 metal salts, respectively. The ligand and its metal complexes were characterized by elemental analysis, FT-IR, 1H-NMR, UV-vis spectra, magnetic measurements and thermal analysis (TGA-DTA) techniques. All complexes were diamagnetic and binuclear. The Co(II) complex was oxidized to Co(III). While suggested structures of Cu(II) and Ni(II) complexes were found as square-planar, Co(III) and Cd(II) complexes were found as octahedral geometries. © 2015, Chemical Society of Pakistan. All rights reserved.
Keywords: Amino vic-dioxime ligand; Anti-chloroglyoxime; Thermal analysis.